Total joint replacement in sub-Saharan Africa: a systematic review. (April 2019) - Davies, Peter SE; Graham, Simon M; Maqungo, Sithombo; Harrison, William J
Outcomes of arthroplasty in sub-Saharan Africa are not widely reported. To our knowledge, this systematic review is the first to explore this topic. Scopus, EMBASE, Medline and PubMed databases were searched, utilising MeSH headings and Boolean search strategies. All papers from South Africa were excluded. Twelve papers reporting 606 total hip replacements (THRs) and 763 total knee replacements (TKRs) were included. Avascular necrosis was the most common indication for THR, whereas osteoarthritis was the main indication for TKR. HIV prevalence of up to 33% was seen. Improvements were seen in patient-reported outcome measures in both THR and TKR. The dislocation rate in THR was 1.6%. The deep infection rate was 1.6% for TKRs and 0.5% for THRs. Positive results were reported, with comparable complications to high-income countries. However, there is likely to be significant reporting bias and the introduction of mandatory registries would enable more accurate monitoring across the region.